Superoleophobic Slippery Lubricant‐Infused Surfaces: Combining Two Extremes in the Same Surface. Issue 45 (30th August 2018) - Dong, Zheqin; Schumann, Martin F.; Hokkanen, Matti J.; Chang, Bo; Welle, Alexander; Zhou, Quan; Ras, Robin H. A.; Xu, Zhenliang; Wegener, Martin; Levkin, Pavel A.
Abstract: The ability to create superoleophobic surfaces repellent toward low‐surface‐tension liquids is important for various applications, and has been recently demonstrated using re‐entrant or doubly re‐entrant microtopography. Liquid droplets on such surfaces feature composite liquid–solid–air interfaces, whereas composite liquid–lubricant–air interfaces would have potential for additional repellency. Here, the development of a novel slippery superoleophobic surface with low adhesion is demonstrated via combining doubly re‐entrant microtopography with slippery lubricant‐infused porous surfaces. This is realized by using 3D direct laser writing to fabricate doubly re‐entrant micropillars with dedicated nanostructures on top of each pillar. The top nanostructures stabilize the impregnated slippery lubricant, while the re‐entrant geometry of the micropillars prevents lubricant from spreading. The slippery layer reduces the adhesion of liquid to the pillars, as proved using scanning droplet adhesion microscopy (SDAM), while the doubly re‐entrant micropillars make the surface superoleophobic. This novel interface combining two extremes, superoleophobicity and slippery lubricant‐infused surface, is of importance for designing superoleophobic and superhydrophobic surfaces with advanced liquid repellent, anti‐icing, or anti‐fouling properties. Abstract : A superoleophobic slippery lubricant‐infused surface is realized by combining doubly re‐entrant microtopography with a slippery lubricant‐infused nanostructured surface. This novel interface is important in the design of surfaces with advanced liquid‐repellent, anti‐icing, or anti‐fouling properties.